Use of cutaneous silent period parameters as a diagnostic indicator in patients with restless legs syndrome-a study in south Indian population - Reena Alexander; Saraswathy L; Siby Gopinath (International Journal of Medical Research and Review, 2018)
Objective: The objectives of this study were to investigate cutaneous-silent- period (CSP) parameters- CSP latency and CSP duration in patients with ‘Restless legs Syndrome’ and compare it with that of normal healthy controls.Methods: Thirty patients diagnosed with restless legs syndrome were included in this study. The cutaneous silent period was evoked by electrical stimulation of sural nerve whereby both CSP parameters CSP latency and CSP duration were recorded and analyzed.Results: The mean latencies of CSP among the thirty RLS patients were 101.95±12.12 while the control group showed 96.23± 9.16. There is a statistically significant high average latency in RLS patients (101.95± 12.12) than control group (96.23± 9.16) with p value=0.044. This study also showed the average CSP duration to be high in RLS patients (42.25± 11.12), when compared to the control group – 36.75± 8.35 (p value=0.035).Conclusion: While RLS is a common sensorimotor disorder, the diagnosis of RLS is purely clinical and there are no objective tests for the diagnosis. Unfortunately, the awareness is poor among the lay population, general practitioners and even specialists in the Indian subcontinent. The authors feel that the CSP test can be used as an objective method supporting the diagnosis of RLS. Furthermore, we believe that this paper will help create awareness in addition to encouraging more research in this arena from medical personnel in India.